Standard model as a Wilsonian effective theory - Zhang, Jiahao (Nanyang Technological University, 2020)
Quantum Field Theory provides a fundamental framework for modelling and predicting experimental results in high energy particle physics. However, the calculated quantities often diverge, and so a renormalisation framework was introduced to extract meaningful, finite quantities from the theory. In the process, counterterms have to be introduced to cancel off the diverging terms. In renormalisable theories, all divergences can be absorbed into the redefinitions of the mass, field and the coupling constant, but this fact would seem to fortuitous. Wilsonian effective field theory gave a different interpretation of the framework and gave physical insight into how it worked. In this report, an introduction to field theory is presented and a discussion of the Wilsonian effective theory